2004
DOI: 10.1590/s1516-89132004000600011
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisins B1 and B2 in corn-based products commercialized in the state of Santa Catarina - Southern Brazil

Abstract: Corn flour, "canjica" (corn grits), corn flakes and popcorn for human consumption, commercialized in Santa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
0
12
2
2
Order By: Relevance
“…These levels are lower than those observed in previous studies conducted in São Paulo and Santa Catarina states showing FB 1 at levels up to 5453 mg kg À1 (Machinski & Soares, 2000;Scaff & Scussel, 2004), hence indicating better quality control practices in the manufacture of corn products in the regions studied.…”
Section: Analysis Of Fumonisin B 1 In Human Haircontrasting
confidence: 70%
See 1 more Smart Citation
“…These levels are lower than those observed in previous studies conducted in São Paulo and Santa Catarina states showing FB 1 at levels up to 5453 mg kg À1 (Machinski & Soares, 2000;Scaff & Scussel, 2004), hence indicating better quality control practices in the manufacture of corn products in the regions studied.…”
Section: Analysis Of Fumonisin B 1 In Human Haircontrasting
confidence: 70%
“…FB 1 contamination in Brazilian corn products has been reported by several authors (Martins et al, 2012;Moreno et al, 2009;Scaff & Scussel, 2004;Westhuizen et al, 2003). Studies on the human exposure of fumonisin through the diet have been conducted in urban areas of São Paulo and Santa Catarina States, and the resulting probably daily intake (PDI) varied from 63.3 to 1276 ng kg À1 body weight (b.w.)…”
Section: Introductionmentioning
confidence: 82%
“…The south and western regions of the Santa Catarina State, where there is a high volume of maize production and heavy consumption of maize byproducts, also have the highest incidence of oesophageal cancer. Maize and maize-based food samples from Paranà and the southeast (São Paulo) contained fumonisin B 1 and fumonisin B 2 at concentrations up to 12 mg g À1 and 10 mg g À1 , respectively (Scaff & Scussel, 2004). An epidemiological study in Rio Grande do Sul indicated that smoking, alcohol and maté drinking, farm work, and having a father with cancer were more frequent in cases of oesophageal cancer (Dietz, Pardo, Furtado, Harzheim, & Furtado, 1998).…”
Section: Toxic Effects On Human Healthmentioning
confidence: 99%
“…Outros estudos preliminares reportaram elevados níveis de FB 1 em produtos derivados de milho no Brasil (SCAFF;SCUSSEL, 2004; VAN DER WESTHUIZEN et al, 2003), indicando que o menor conteúdo encontrado no presente estudo pode ser consequência de melhores práticas de controle de qualidade pelas empresas de processamento de produtos de milho no estado de São Paulo, para cumprir com a regulação vigente para fumonisinas. As diferenças nos níveis de ação de fumonisinas em todo o mundo reflete a preocupação geral de que os governos têm sobre os potenciais efeitos das micotoxinas sobre a saúde humana e suas implicações econômicas (FAO, 2003).…”
Section: Avaliação De Fb 1 Em Amostras De Alimentosunclassified
“…A produção anual de milho no Brasil girou em torno de 53 milhões de toneladas na safra de 2009/2010, sendo o terceiro maior produtor mundial do referido grão (MAPA et al, 2015). Estudos realizados anteriormente no Brasil demonstraram a elevada incidência de contaminação por fumonisinas no milho e derivados, chegando a 100% de incidência em alimentos comercialmente disponíveis SCUSSEL, 2004;BITTENCOURT et al, 2005;MARTINS et al, 2012).…”
Section: Introductionunclassified